2005
DOI: 10.1055/s-2005-837493
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroid‐Promoted Growth

Abstract: Brassinosteroids (BRs) are highly potent growth-promoting sterol derivatives. BR-deficient or BR-insensitive mutants display dwarfism. Whole plants and excised tissues have been used to analyse the mechanisms involved in BR-promoted growth. BR stimulates cell elongation and cell division, and BR has specific effects on differentiation. Underlying physiological pathways include modification of cell wall properties, effects on carbohydrate assimilation and allocation, and control of aquaporin activities. BR appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 99 publications
2
70
0
Order By: Relevance
“…A recent study has demonstrated that auxin transport through the nonhair cells controls the elongation of root hairs in the hair cell position (10). Global transcriptome analysis of whole seedlings revealed that expression of WER can be induced by treatment with brassinosteroids (BRs) (11), a class of steroid hormones known to promote growth in diverse plant species (12). Although BRs are known to affect root elongation (13), no previous work has connected them to the root hair formation program.…”
mentioning
confidence: 99%
“…A recent study has demonstrated that auxin transport through the nonhair cells controls the elongation of root hairs in the hair cell position (10). Global transcriptome analysis of whole seedlings revealed that expression of WER can be induced by treatment with brassinosteroids (BRs) (11), a class of steroid hormones known to promote growth in diverse plant species (12). Although BRs are known to affect root elongation (13), no previous work has connected them to the root hair formation program.…”
mentioning
confidence: 99%
“…21) BRs may also affect fertilization by stimulating filament and pollen growth and modifying pollen properties. 22) Sheoran and Saini reported that normal starch accumulation during pollen development was strongly inhibited in stressful environments and caused nonviable pollen.…”
Section: Discussionmentioning
confidence: 99%
“…Elongation growth is mainly mediated via gibberellins (GAs) and brassinosteroids (BRs) (reviewed in Phinney 1985;Müssig 2005), which stimulate internode elongation (Yamamuro et al 2000;Dayan et al 2012;Li et al 2012). Ethylene signaling has been shown to influence internode elongation in rice adapted to deep water conditions (Hattori et al 2009;Qi et al 2011), and IAA contributes to elongation growth in pea (McKay et al 1994).…”
Section: Genetic Control Of Plant Architecture In Herbaceous Plantsmentioning
confidence: 99%